Probabilistic Seismic Hazard Analysis on Dam Site for specific Hydraulic Structure - P. Shrestha; P.M. Pradhan; S.P. Timalsina (International Association of Lowland Technology, 2020)
In this research, the probabilistic seismic hazard analysis has been carried out at Upper Seti hydropower, located at Damauli, Tanahu District; western part of Nepal. The earthquake magnitudes and epicenter list; earthquake catalog were collected from various sources and then the declustering of earthquake data was performed. The seismic source zone around the site within 300km radius has been taken reference for seismic source model. Similarly relationship between magnitude and frequency of earthquake has been developed to obtained Guttenberg and Richter ‘a’ and ‘b’ parameters. Adopting suitable attenuation relationship and obtaining different probability densities and the seismic hazard curve has been developed for the dam site area where hydraulic structure is to be located. Finally, various levels of Peak Horizontal Acceleration (PHA) are obtained for various return periods using hazard curve at the dam site.